Prognostic value of the oxygenation index to predict survival in infants with congenital diaphragmatic hernia - Sarkhan Elbayiyev; Esra Beser; Gulsum Kadioglu Simsek; Bengu Karacaglar; Hayriye Gozde Kanmaz Kutman; Fuat Emre Canpolat (EL-Med-Pub, 2022)
Background: Congenital Diaphragmatic Hernia (CDH) is associated with significant morbidity and mortality. We aimed to investigate the relationship between survival and oxygenation index calculated in the first 12 hours of life in neonates with CDH.  Methods: Various scoring systems have been developed to predict and determine the course of the disease in this disease group with a high mortality rate. In our study, we planned to investigate the use of APGAR scores, Neonatal acute physiological perinatal spread score-II, and oxygenation index in predicting survival. Patients born in Ankara City Hospital between March 2019 and November 2021 and followed up due to congenital diaphragmatic hernia were included in the study. Preductal oxygen saturation (sPO2) was manipulated to be 80-95% and postductal >70%. Target PaCO2 values were set to be 50-70 mmHg. Oxygenation index scores were calculated using the formula mean airway pressure (MAP) (cmH2O) x fraction of inspired oxygen (FiO2) (%) / partial pressure of arterial oxygen (PaO2) (mmHg). Results: The 5th-minute APGAR scores of the patients with the congenital diaphragmatic hernia in our study were lower in the non-survivors group than the survivors group (p=0.010). SNAPPE-II and OI scores were statistically significantly higher in the nonsurvivors group (p=0.003 and p=0.002). Conclusion: The oxygenation index was determined to be an independent predictive parameter in mortality (OR: 4.519 CI: 1.301-654.645, p=0.034). The results of our study show that the oxygenation index is a reliable parameter in predicting survival.